Expression of Hsp70 and β-actin Genes as The Immune Response against Viral Nervous Necrosis that Infected Asian Seabass (Lates calcalifer) - Wahyudi, Yusuf Arif; Yanuhar, Uun; Maftuch, Maftuch (Graduate School, Universitas Brawijaya, 2018)
The viral nervous necrosis (VNN) is betanodavirus of the family Nodaviridae with acute infection and associated with high levels mortality up to 100% of numerous larval-stage marine and freshwater fish species. The danger signals of viral infection that are capable of activating APCs (Antigen Presenting Cells), furthermore produced molecules protein receptors such as interferon and heat shock proteins. Stimulating interferon type I (IFN I) induce several antiviral molecules, further binding the actin cytoskeleton to reach the site of infection. This study demonstrated a correlation between increased levels of Hsp70 (heat shock proteins) and actin filamentous (β-actin) within invasion wild-type isolate of ssRNA VNN from Asian Seabass (L. calcalifer) juvenile. Furthermore, expression of Hsp70 and actin as an indicator or biomarker of stressed states in fish. The reverse transcriptase polymerase chain reaction (RT-PCR) method used to finding expression Hsp70 and β-actin. Whereas nested RT-PCR used for VNN genes. The up-regulation of Hsp70 was observed on the brain tissue higher than eye tissue of sample positive infected VNN. Whereas different expression of β-actin, β-actin receptor expression tends to be stable in the organs of the brain and eye, both invaded VNN or normal, while on the eye, the ratio slightly increased based on the intensity of the band. The research shows that altered expression of heat shock protein 70 and beta-actin gene receptors in the target organs that response to invasion VNN at Asian seabass (L. calcalifer) juvenile. Alteration expression of heat shock protein 70 and beta-actin can be used as an indicator or biomarker of stress cells, especially from VNN invasion at fish. Keywords: Asian seabass, β-actin, Hsp70, Immune response, Viral nervous necrosis.